Relationship of pesticide spraying to signs and symptoms in Indonesian farmers - Kishi, M.; Hirschhorn, N.; Djajadisastra, M.; Satterlee, L. N.; Strowman, S.; Dilts, R. (Scandinavian Journal of Work, Environment & Health, 1995)
' ' OBJECTIVES ': 'This study assessed correlations between exposure to pesticides and signs and symptoms of pesticide toxicity among Indonesian farmers.' ' METHODS ': 'Detailed observations were recorded of spray frequency and pesticide handling, dermal exposure, and the chemicals used. Symptoms of acute illness were reported by the farmers, and signs of poisoning were observed by the interviewers at the time of spraying or within a few hours after it.' ' RESULTS ': 'The spray practices substantially exposed the farmers to pesticides. Signs and symptoms occurred significantly more often during spraying than during nonspraying seasons. Twenty-one percent of the spray operations resulted in three or more neurobehavioral, respiratory, and intestinal signs and clothes being wetted with the spray solutions were significantly and independently associated with the number of signs and symptoms. A dose-effect relationship was found between the neurobehavioral signs and symptoms and the use of multiple organophosphates.' ' CONCLUSION ': 'For farmers in the tropics, fully protective garb is too hot and too costly to maintain; farmers thus accept illness as a necessity. Integrated pest management has previously been demonstrated to reduce pesticide use with no loss of crop yield. The frequency of spraying should be reduced through widespread training in integrated pest management, and also the licensing and sale of the most hazardous pesticides should be regulated.
Keywords: exposure; farmer; hazard grades; Indonesia; integrated pest management; pesticide spraying; poisoning; symptom; WHO; World Health Organisation